2016
DOI: 10.1371/journal.pntd.0004614
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Forms of Leishmania amazonensis Excreted/Secreted Promastigote Surface Antigen (PSA) Induce Protective Immune Responses in Dogs

Abstract: Preventive vaccination is a highly promising strategy for interrupting leishmaniasis transmission that can, additionally, contribute to elimination. A vaccine formulation based on naturally excreted secreted (ES) antigens was prepared from L. infantum promastigote culture supernatant. This vaccine achieved successful results in Phase III trials and was licensed and marketed as CaniLeish. We recently showed that newly identified ES promastigote surface antigen (PSA), from both viable promastigotes and axenicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…Interestingly, ES from L. infantum elicited a protective immune response in dogs, their natural hosts, by triggering a Th1-dominant immune response and an appropriate specific antibody response, thereby countering the parasite-induced arginase metabolism early on, and leading to the first anti-Leishmania vaccine commercially available in Europe ( 159 161 ). More recently, a secreted promastigote surface antigen, one of the main constituents and the highly immunogenic antigen of Leishmania , was shown to confer high levels of protection in naive dogs ( 162 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ES from L. infantum elicited a protective immune response in dogs, their natural hosts, by triggering a Th1-dominant immune response and an appropriate specific antibody response, thereby countering the parasite-induced arginase metabolism early on, and leading to the first anti-Leishmania vaccine commercially available in Europe ( 159 161 ). More recently, a secreted promastigote surface antigen, one of the main constituents and the highly immunogenic antigen of Leishmania , was shown to confer high levels of protection in naive dogs ( 162 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that LetiFend ® can prevent the development of leishmaniasis in six-month-old dogs after natural infection with Leishmania infantum [101]. Recently, it was shown that the administration of recombinant ES LaPSA-38S (rPSA) or its carboxy terminal part (LaPSA-12S, Cter-rPSA), combined with QA-21 as adjuvant, conferred high levels of protection against L. infantum in beagles, as evidenced by a significant decrease in parasite burden and an increase in the Th1 immune response [102] Cross protection has been reported in vaccine studies in canine leishmaniasis. Roatt et al observed that the administration of a vaccine comprising of L. braziliensis antigens with saponin as an adjuvant (LBSap vaccine) conferred protection to dogs challenged with L. infantum mixed with salivary gland extracts.…”
Section: Advances In Vaccination Against Leishmaniasismentioning
confidence: 99%
“…In addition, administration of major immunogenic proteins provides path to generate integrated immune responses, especially against specified protective antigens. 124 …”
Section: Introductionmentioning
confidence: 99%